Integrated assessment of scale impacts of watershed intervention assessing hydrogeological and bio-physical influences on livelihoods - Reddy, V. Ratna; Syme, Geoffrey J. (Amsterdam Elsevier, 2014)
Integrated Assessment of Scale Impacts of Watershed Interventions is the outcome of a multi-disciplinary research team of social scientists, hydrologists (groundwater and surface water), modellers; and bio-physical scientists who have worked together over five years to develop an integrated model of the sustainability of biophysical, economic and social impacts of watersheds. Impacts of watershed interventions are assessed at upstream, mid-stream and downstream locations of two hydrological units that are characterised with differential bio-physical attributes. The editors propose that watershed interventions, when integrated with hydro-geology and bio-physical aspects, have greater influence on the resilience of the socio-ecological system. This book takes these aspects in to consideration and in the process provides insights in to watershed design and implementation.--Provided by publisher.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Watershed management; Watershed management -- Economic aspects; Soil conservation; Electronic books